Analisa Strategi Marketing untuk Meningkatkan Profitabilitas UD. Mumani dengan Menggunakan Analisa SWOT di Era Pandemi Covid-19 - Setyariningsih, Eny; Hidayat, M. Syamsul (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
Marketing Strategy is the right strategy to increase sales volume at UD. Numani. So the aim of this research is to find out the marketing strategy implemented by UD. Numani is able to influence the profitability of its income, by carrying out internal and external analysis, as well as finding out the right strategy to increase sales by using SWOT analysis. This type of research is descriptive qualitative research located at UD. Numani Mojokerto. The data collection technique involves conducting interviews with the owner, observing and documenting. Then the data is analyzed through SWOT analysis by identifying internal and external factors, then calculating the IFAS (Internal Factor Analysis Strategic) matrix and EFAS (External Factor Analysis Strategic) matrix, as well as providing recommendations for strategies through the results of calculating the SWOT matrix. The results of this research found that UD. Numani is in Kwadran II position and is very likely to be able to implement marketing development strategies and product development strategies. This research also identifies internal and external factors which will then be analyzed using the SWOT matrix to produce a strength value of 3.67, weakness 1 .49, opportunity 2.49, and threat 3.73 from the results show that UD. Numani is in quadrant II or what is usually called the progressive quadrant. This position indicates that an organization is in prime and stable condition so that it is possible to continue developing various aspects, especially marketing and product development, increasing marketing reach by using and implementing online marketing strategies.